ANALISIS IMPLEMENTASI KEBIJAKAN,PAJAK PERTAMBAHAN NILAI ATAS TRANSAKSI E-COMMERCE PADA KPP MADYA JAKARTA SELATAN I TAHUN 2021 - Amelia, Melda; Pribadi Agustianto, Jiwa; Dwi Yanuar, Ryan (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The development of technology and communication, especially with the presence of the internet, is increasingly being used by many parties to conduct online transactions, for example, shopping or selling online, or what is called e-commerce. The significant increase in e-commerce transactions in Indonesia has not escaped the government's attention as it is related to tax collection. This study aimed to analyze the implementation of value added tax policy on e-commerce transactions and to find out the efforts made to overcome the obstacles faced in the implementation of the value added tax policy on e-commerce transactions at South Jakarta Medium Tax Office I. This study was conducted at South Jakarta Medium Tax Office I using a qualitative descriptive approach to describe information about the implementation of value added tax policy on e-commerce transactions in South Jakarta Medium Tax Office I. The data collection was by observation, interviews, and documentation. The informants of this study were the Account Representative of South Jakarta Medium Tax Office I, Lecturer at Stiami Jakarta Institute of Social Sciences and Management, and e- commerce taxpayers. The data analysis technique in this study used Miles and Huberman data analysis. The results of the study showed that the implementation of the value added tax policy on e-commerce transactions at the South Jakarta Medium Tax Office I in 2021 cannot be said to be optimal as a whole because there is still a lack of human resources at the South Jakarta Medium Tax Office I regarding technology systems so that it is difficult to collect integrated and comprehensive virtual data from e- commerce.